2011
DOI: 10.1021/am200428v
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Graphene Oxide and Graphene in Human Erythrocytes and Skin Fibroblasts

Abstract: Two-dimensional carbon-based nanomaterials, including graphene oxide and graphene, are potential candidates for biomedical applications such as sensors, cell labeling, bacterial inhibition, and drug delivery. Herein, we explore the biocompatibility of graphene-related materials with controlled physical and chemical properties. The size and extent of exfoliation of graphene oxide sheets was varied by sonication intensity and time. Graphene sheets were obtained from graphene oxide by a simple (hydrazine-free) hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
944
5
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,244 publications
(1,052 citation statements)
references
References 36 publications
54
944
5
7
Order By: Relevance
“…Liao and co-workers have shown that graphene oxide displays minimal cytotoxicity towards human erythrocytes and skin broblast cells, however graphite oxide and reduced graphene oxide were shown to inhibit cell growth. 229 These results agree well with the anti-bacterial properties observed for certain graphene materials. Additionally, cytotoxicities of graphene and graphene-based materials have also been tested in mice cell lines and have been shown to have negligible toxicity at low concentrations.…”
Section: Environmental and Biological Toxicity Of Graphenesupporting
confidence: 86%
See 2 more Smart Citations
“…Liao and co-workers have shown that graphene oxide displays minimal cytotoxicity towards human erythrocytes and skin broblast cells, however graphite oxide and reduced graphene oxide were shown to inhibit cell growth. 229 These results agree well with the anti-bacterial properties observed for certain graphene materials. Additionally, cytotoxicities of graphene and graphene-based materials have also been tested in mice cell lines and have been shown to have negligible toxicity at low concentrations.…”
Section: Environmental and Biological Toxicity Of Graphenesupporting
confidence: 86%
“…Multiple recent studies have focused on the use of graphene and graphene composites in biomedical applications. 133,[228][229][230][231] From these studies, as well as other cytotoxicity studies on graphene and related compounds, 69,232-251 we are able to draw some conclusions regarding graphene's biological toxicity.…”
Section: Environmental and Biological Toxicity Of Graphenementioning
confidence: 91%
See 1 more Smart Citation
“…[11] The effect of simvastatin on hematotoxicity induced by GO/ AgNPs is a crucial indicator to evaluate therapy. [41,42] Herein, the effect of simvastatin to RBCs induced by GO/AgNPs was evaluated by the observation of optical microscopy and scanning electron microscopy (SEM) (Figure 3). As compared with the normal RBCs, the images of microscopy and SEM show the existence of damaged RBC after exposure to 1 mg per kg bw of GO/AgNPs.…”
Section: Effect Of Simvastatin On In Vivo Toxicity Induced By Go/agnpsmentioning
confidence: 99%
“…To study the materials' toxicity, A549 cells were exposed to the test materials and the remaining cell viabilities were measured using WST-8 assay.W ST-8, am itochondrial activity-based assay,w orks on the principle that soluble formazan is produced due to cellular reduction by dehydrogenase activities in viable cells. [10,[46][47][48] By normalising the absorbance intensities obtained with ac ontrols etup, where cells were not treated with any test materials, the extent of toxicity exhibited by the Group 5 ditellurides towards A549 cellsc ouldb ed etermined. Data collected from the WST-8 assay is illustrated in Figure 3.…”
Section: Cytotoxicity Assessmentmentioning
confidence: 99%